Análise do desempenho da técnica de reforço NSM (Near Surface Mounted) com fibras de carbono em vigas submetidas à flexão - Wierzbicki, Luisa Rocha (2021)
Reinforced concrete structures have been optimized for lower costs. With slender sections, such elements are more sensitive to material defects, executive or design errors, which can often lead to the appearance of pathologies. Thus, the need for reinforcement and recovery of reinforced concrete elements is increasingly frequent. Among the structural reinforcement methods used in Brazil, there is reinforcement with Carbon Fiber-Reinforced Polymer (CFRP). In this sense, it is proposed to analyze the performance of the Near Surface Mounted (NSM) technique for the application of carbon fiber composite reinforcement, in beams subjected to simple bending effort. For this, twenty-one samples were molded, nine with real dimensions – Group B (15x25x220cm) and twelve on a reduced scale – Group A (10x17.5x50cm), of beams without reinforcement application, with reinforcement of CFRP blanket applied externally – EBR technique (Externally Bonded Reinforcement) and with reinforcement of CFRP sheets applied in the concrete covering section – NSM technique. All rehabilitated beams were subjected to the four point bending test until the ultimate loads were obtained, for which comparisons were made between the reinforcement techniques and, also, the theoretical resistant capacities. Group A beams reinforced by the EBR technique resisted a load approximately 69% higher than the load supported by the reference beams, whereas those reinforced by the NSM technique presented a 46% higher load than the reference beams. In Group B, some samples of the beams reinforced by the EBR technique showed deficiency in the ruin load, a fact that led to an increase of only 6% in the resistant capacity, while for those reinforced with the NSM technique, was obtained a load increase of 36%, when compared to reference beams. In addition, there was also an increase in stiffness of the beams with the application of reinforcement by the two techniques studied. Still, from the Analysis of Variance (ANOVA) it was possible to verify that the reduced samples are statistically equal to those in real scale, being viable mainly for initial studies, because they allow the production of a greater quantity and variety of samples with the same quantity of inputs and also bring great advantages regarding the handling of parts.